Intelligent alarm system for monitoring at LRT station - Norshakila, Mohamad Sharif (2010)
Objective of this project was to explore how the advantages of new technological solutions can be fully exploited and provide opportunities for the enhancement of security management. Every day millions of commuters use rail public transportation to get to work, and businesses rely on millions of miles of railroad track for transporting goods efficiently and safely. Users of rail public transport demand a safe and secure environment, one without any feeling of threat. Unfortunately, that is not the reality in many places. While safety is usually of a high standard, the feeling of personal security is often diminished. This discourages people from using rail public transport, and for many people it restricts their mobility. Traditionally, this has meant an operating company deploying staff and monitoring systems to carry at manual based surveillance of the environment to prevent undesirable events and to reassure the travelling public that they are in a safe and secure environment. By using some methods to detect situations of interest using automated image processing, the result show the capability of automatic systems to detect potentially dangerous situations and of a distributed system that can promptly alert operators providing multiple sensor views of event.